Analisis Pengaruh Penggunaan E-Banking Dan Fitur Produk Terhadap Kepuasan Nasabah Bank Rakyat Indonesia Di Kecamatan Jombang - Ita Rahmawati; Elva Fitria Ningrum; Lailatus Sa'adah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This research is included in quantitative research, which aims to determine the effect of using e-banking and product features on customer satisfaction of Bank Rakyat Indonesia in Jombang District. This research uses associative descriptive research. Associative research is research that aims to determine the relationship between two or more variables. The sample is part of the number and characteristics possessed by the population, the determine of the number of samples in this study uses the lameshow formula, thus for an infinite or detectable population, a minimum of 100 respondent can be used. With non-probability sampling tecnique because the research does not have definite data about population size and complete information about elements. Based on the research results, the e-banking variable has a positive direction. Meanwhile for the calculation of T arithmetic obtainet by -0,801 T tabel 1,984 then -0,801 > 1,984. And the value of sig (0,425 > 0,05) then Ho is accepted, Ha is rejected, then e-banking has no effect on customer satisfaction. The product feature variabel has a regression coefficient of 0,656. This indicates that the value has a positive direction. Meanwhile, for the calculation of T arithmetic obtained by 7,476 T tabel 1,984 then 7,476 > 1,984. And the value of sig (0.000 < 0,05) then Ho is rejected, Ha is acceped. So product features have a significant effect on customer satisfaction